Pengaruh Pengembangan Terhadap Kinerja Guru dengan Kepuasan Kerja sebagai Variabel Intervening pada SMK Negeri 1 Muaro Jambi - Alfredo, Muhammad Fatur; Adriani, Zulfina; Sumarni, Sumarni (STIKes Ibnu Sina Ajibarang, 2025)
This research examines the impact of development on teacher performance, with job satisfaction serving as a mediating variable at SMK Negeri 1 Muaro Jambi. The approach used in this research is quantitative, and data collection was done through questionnaires from 58 teachers. The findings indicate that development has a positive impact on teacher performance, both directly and indirectly through job satisfaction as a mediating variable. Job satisfaction also plays a significant role in enhancing teacher performance. This study showed that with proper designs, the development programs improve job satisfaction and motivational levels among the teachers. Development of training, adequate reward, and appropriate job variation may improve the state of affairs for increasing satisfaction and teacher productivity. All this was hoped to become inputs into the human resource management aspect of educational institutions.